1977
DOI: 10.1063/1.323646
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of heating and burst phenomena in electrically exploded foils

Abstract: A method is presented for computing the transient current and temperature distributions in electrically exploded foils. The model employed is applicable up until the time of burst. Calculations are presented for Al, Cu, and Au foils showing good agreement with experimental current waveforms and burst times over a wide range of capacitor-bank charging voltages and for varying foil cross sections. The two-dimensional nature of the calculation permits investigation of effects associated with nonuniform heating of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1979
1979
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The magnetic contribution to the velocity was estimated by assuming infinite plane conductors and integrating the equation Wc + PmdmlX W (11) where p c , d c , and p m , d m are the density and thick ness of the foil and flyer material, respectively, X is the current per unit width calculated from Equation 1; H 0 is the permittivity of free space; and X is the acceleration of the foil and flyer. If the magnetic and hydrodynamic contributions to the flyer velocity are separable, subtracting the magnetic contribution from a measured velocity-time curve should leave the hydrodynamic contribution.…”
Section: Magnetic Acceleration Effects the Dependence Of Electrical Gmentioning
confidence: 99%
“…The magnetic contribution to the velocity was estimated by assuming infinite plane conductors and integrating the equation Wc + PmdmlX W (11) where p c , d c , and p m , d m are the density and thick ness of the foil and flyer material, respectively, X is the current per unit width calculated from Equation 1; H 0 is the permittivity of free space; and X is the acceleration of the foil and flyer. If the magnetic and hydrodynamic contributions to the flyer velocity are separable, subtracting the magnetic contribution from a measured velocity-time curve should leave the hydrodynamic contribution.…”
Section: Magnetic Acceleration Effects the Dependence Of Electrical Gmentioning
confidence: 99%
“…The traditional material of EFIs is copper, aluminum, gold, which has low melting temperature, high electrical resistivity. Researchers have made extensive investigations for metallic foil with high current pulse and accelerating flyer process, including experimental and simulation [10][11][12][13][14]. For the metallic foil process in high current pulse, it has been developed a magnetohydrodynamics (MHD) code to calculate the discharging current waveforms, voltage across the bridge foil region, plasma pressure, and flyer velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in most applications, the metal bridge foil connection area is generally a single bridge structure with an approximately square shape [2][3][4][5][6][7][8]. Many theoretical and experimental studies have been conducted on the influence of bridge material, size, and the corner shape of the bridge connection on the electrical explosion performance, and some valuable results have been obtained [9][10][11][12][13][14][15][16]. In other shape research conducted in the United States, Neyer et al [17] designed a ring bridge structure of a single bridge foil, and showed that the ring structure can produce a flatter flyer, which is more conducive to initiate the explosive.…”
Section: Introductionmentioning
confidence: 99%